Sentiment analysis for Malay language: systematic literature review - Handayani, Dini; Awang Abu Bakar, Normi Sham; Yaacob, Hamwira Sakti; Abuzaraida, Mustafa Ali (Institute of Electrical and Electronics Engineers Inc., 2018)
Recent research and developments in Sentiment Analysis (SA) have simplified sentiment detection and classification from textual content. The related domains for these studies are diverse and comprise fields such as tourism, costumer review, finance, software engineering, speech conversation, social media content, news and so on. SA research and developments field have been done on various languages such as Chinese and English language. However, SA research on other languages such as Malay language is still scarce. Thus, there is a need for constructing SA research specifically for Malay language. To understand trends and to support practitioners and researchers with comprehension information with regard to SA for Malay language, this study exhibit to review published articles on SA for Malay language. From five online databases including ACM, Emerald insight, IEEE Xplore, Science Direct, and Scopus, 2433 scientific articles were obtained. Moreover, through the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) Statement, 10 articles have been chosen for the review process. Those articles have been reviewed depend on a few categories consisting of the aim of the study, SA classification techniques, as well as the domain and source of content. As a result, the conducted systematic literature review shed some light about the starting point to research in term of SA for Malay language.